The Impact of Leadership and Supervision on Morales and Performance of Civil Servants at The Office for Management of Regional Revenue, Finance and Assets of Pekanbaru - Pratama, Dafitra; Hendriani, Susi; Efni, Yulia (Program Pascasarjana, Universitas Riau, 2017)
The objectives of these study is to get a better knowledge of the impact of leadership and supervision on the civil servants morale and performance at the office for Management of Regional Revenue, Finance and Assets of Pekanbaru. Variables used in this research are leadership and supervision as independent variables while morale and performance as dependent variables. Sampling method used in this research is sampling census method with a sample of 124 people working in the office of Management of Regional Revenue, Finance and Assets of Pekanbaru. Statistical analysis used to test the impact of leadership and supervision on the civil servant morale and performance is a WarpPls analysis, which explains the relationship between variables either directly or indirectly. The results of this study indicate that leadership has a direct impact on the civil servant performance and it has indirect impact on the civil servant performance through morale. Supervision has an impact on the civil servant performance and it has no indirect impact on the civil servant performance through morale. The morale has a direct impact on the civil servant performance.